The Influence of Tax Knowledge, the E-Samsat (Sapa Warga) Payment Program, and the Motor Vehicle Tax Amnesty Program on Motor Vehicle Taxpayer Compliance (Case Study at the PPPD Office of Sukabumi Region I Cibadak) - Aryani, Ririn Sri; Hendaris, R. Budi (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study investigates how tax knowledge, the E-Samsat payment system (Sapa Warga), and vehicle tax amnesty programs influence taxpayer compliance among motor vehicle owners in the Sukabumi I Cibadak Regional Revenue Management Center. Using a quantitative approach, researchers surveyed 100 taxpayers and applied multiple linear regression for data analysis. The findings reveal that tax knowledge has positive and influential on taxpayer compliance, indicating that individuals with a stronger understanding of tax obligations, regulations, and sanctions usually take care of their taxes properly. Conversely, the E-Samsat payment system is uninfluential toward compliance levels, suggesting that digital convenience alone may not be sufficient without supporting factors such as public awareness, trust in the system, and adequate digital literacy. Meanwhile, Tax Amnesty Program has a beneficial and influential effect toward compliance levels. Despite the limited impact of E-Samsat as a standalone variable, simultaneous testing of all three predictors indicates a collective and influential on taxpayer compliance. The study concludes by emphasizing the need for a multi-branch strategy that integrates tax education, effective digital service dissemination, and incentive-based policies.